87 Effect of Number of Source Litters Used to Create Cross-fostered Litters on Piglet Pre-weaning Mortality and Weaning Weight - Vande Pol, Katherine D (J Anim Sci, 2021)
Sow litter sizes have increased over recent decades, increasing the need for cross-fostering. The objective of this study was to determine the effect of the number of source litters used to create cross-fostered litters on piglet pre-weaning mortality (PWM) and weaning weight. A RCBD was used with 26 blocks of 5 litters (total 130 litters/1820 piglets), all litters consisted of 14 piglets. Blocking factors were farrowing day, sow parity, body condition score, and functional teat number, and the average and CV of piglet birth weight. Five cross-fostering treatments were compared: 0%, 1 source (all piglets remaining on the birth sow); 100%, 1 source (all piglets moved from birth to a different sow); 100%, 6+ sources (piglets from ≥ 6 birth sows used to form a litter on a different sow); 50%, 2 sources (7 piglets remaining with birth sow, 7 from one other sow); 50%, 4+ sources (7 piglets remaining with the birth sow, 7 from ≥ 3 other sows). The single-source litters were selected from those with > 14 piglets at birth, with excess piglets removed. For other treatments, piglets were selected to meet blocking factors. Piglets were weighed 24 h after birth and at weaning (19.5 ± 0.50 d); all PWM was recorded. Weight data were analyzed using PROC MIXED of SAS; PWM data were analyzed using PROC GLIMMIX of SAS. Models included Treatment and sow within block. There was no effect (P > 0.05) of treatment on weaning weights. Pre-weaning mortality was greater (P < 0.05) for the 0%, 1 source compared to the 50%, 2 source treatment, with the others being intermediate and generally not statistically different (Table 1). In conclusion, cross-fostering and/or mixing litters had no effect on weaning weights, but pre-weaning mortality was highest for the non-fostered treatment. [Image: see text]